THE EFFECT OF WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE IN MEDIATION BY WORK DISCIPLINE AT PT. SINAR SOSRO TANJUNG MORAWA - Indah Lestari; Aulia Arief Nasution (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to determine the effect of the Work Environment on Employee Performance with Work Discipline as a mediating variable at PT. Sinar Sosro Tanjung Morawa. The sample used was 137 respondents. This study uses the Sobel Test as an analysis technique that can justify the influence of independent variables on dependent variables both directly and indirectly through mediating variables. The results of this study indicate that the Work Environment variable partially has a significant effect on Work Discipline, the Work Environment partially has a significant effect on Employee Performance, Work Discipline partially has a significant effect on Employee Performance. The Work Environment also affects Employee Performance indirectly through increasing employee Work Discipline.